2016
DOI: 10.18520/cs/v111/i9/1543-1547
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Case of Ciguatera Fish Poisoning in Mangalore, India

Abstract: Application of LANDSAT data and synoptic remote sensing to predictive models for prehistoric archaeological sites: an example from the Delaware coastal plain. Am. Antiq., 1986, 51, 572-588. 24. Oltean, I. A., Rajani, M. B. and Nalini, N. S., Archaeometallurgy in the Telangana region: a GIS approach in pioneering metallurgy: the origins of iron and steel making in the southern Indian subcontinent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The symptomatology in the hospitalised patients corroborated with earlier reports of ciguatera fish poisoning (Rajeish et al, 2016) with typical clinical signs like gastrointestinal, neurological and cardiovascular symptoms. All six patients (one male and five females) were admitted with CFP symptoms of vomiting, diarrhoea, paraesthesia of upper limbs and lower limbs.…”
Section: Notesupporting
confidence: 86%
“…The symptomatology in the hospitalised patients corroborated with earlier reports of ciguatera fish poisoning (Rajeish et al, 2016) with typical clinical signs like gastrointestinal, neurological and cardiovascular symptoms. All six patients (one male and five females) were admitted with CFP symptoms of vomiting, diarrhoea, paraesthesia of upper limbs and lower limbs.…”
Section: Notesupporting
confidence: 86%
“…Consequently, L. bohar and L. monostigma are known as ciguateric fishes, while L. gibbus and L. fulviflamma are known as non-ciguateric fishes in Okinawa. A previous phylogenetic analysis using DNA barcode data of the cytochrome oxidase subunit I and 16S rRNA genes indicated that L. gibbus is more closely related to L. bohar than to L. fulviflamma [ 23 ]. However, comparison of the in vitro CTX oxidation activities in these fishes suggested that L. bohar and L. gibbus have different metabolic pathways for CTX detoxification, which is assumed to begin with an oxidation reaction; and these differences may lead to species-specific toxin profiles in fish.…”
Section: Discussionmentioning
confidence: 99%
“…In southwest India, CP was not described until 2015 when two successive outbreaks involving red snapper (Lutjanus bohar, locally known as chempalli) occurred in Mangalore (Rajeish et al, 2016;Rajisha et al, 2017b). The first outbreak (June 2015) involved two individuals who became ill following consumption of a red snapper purchased from a local market (Rajeish et al, 2016), whereas the second outbreak (September 2016) affected > 200 people (Karunasagar et al, 2018).…”
Section: Indian Ocean Regionmentioning
confidence: 99%
“…In southwest India, CP was not described until 2015 when two successive outbreaks involving red snapper (Lutjanus bohar, locally known as chempalli) occurred in Mangalore (Rajeish et al, 2016;Rajisha et al, 2017b). The first outbreak (June 2015) involved two individuals who became ill following consumption of a red snapper purchased from a local market (Rajeish et al, 2016), whereas the second outbreak (September 2016) affected > 200 people (Karunasagar et al, 2018). The confirmation of the presence of CTXs in implicated fish samples was further provided using a variety of toxicity methods including mouse bioassay, cytotoxicity and receptor binding assays, and LC-MS/MS (Rajisha et al, 2017a;Rajisha et al, 2017b;Karunasagar et al, 2018) (Table 3).…”
Section: Indian Ocean Regionmentioning
confidence: 99%